Freshwater ecoacoustics as a tool for continuous ecosystem monitoring. Issue 4 (15th March 2018) - Linke, Simon; Gifford, Toby; Desjonquères, Camille; Tonolla, Diego; Aubin, Thierry; Barclay, Leah; Karaconstantis, Chris; Kennard, Mark J; Rybak, Fanny; Sueur, Jérôme
Abstract : Passive acoustic monitoring is gaining popularity in ecology as a practical and non‐invasive approach to surveying ecosystems. This technique is increasingly being used to monitor terrestrial systems, particularly bird populations, given that it can help to track temporal dynamics of populations and ecosystem health without the need for expensive resampling. We suggest that underwater acoustic monitoring presents a viable, non‐invasive, and largely unexplored approach to monitoring freshwater ecosystems, yielding information about three key ecological elements of aquatic environments – (1) fishes, (2) macroinvertebrates, and (3) physicochemical processes – as well as providing data on anthropogenic noise levels. We survey the literature on this approach, which is substantial but scattered across disciplines, and call for more cross‐disciplinary work on recording and analysis techniques. We also discuss technical issues and knowledge gaps, including background noise, spatiotemporal variation, and the need for centralized reference collection repositories. These challenges need to be overcome before the full potential of passive acoustics in dynamic detection of biophysical processes can be realized and used to inform conservation practitioners and managers.